Use of Leishmania major parasites expressing a recombinant Trypanosoma cruzi antigen as live vaccines against Chagas disease - Cai, Catherine W.; O’Shea, Anne; Eickhoff, Christopher S.; Guo, Hongjie; Lewis, Warren G.; Beverley, Stephen M.; Hoft, Daniel F. (Frontiers in Microbiology, 2022)
Trypanosoma cruzi is the protozoan parasite causing Chagas disease, a Neglected Tropical Disease that affects 8 million people and causes 12,000 deaths per year, primarily because of cardiac pathology. Effective vaccination for T. cruzi remains an elusive goal. The use of a live vaccine vector, especially one that mimics the pathogen target, may be superior to the use of recombinant protein or DNA vaccine formulations. Here, we generated recombinant Leishmania major, a related trypanosomatid parasite, as a vaccine vehicle to express the immunogenic T. cruzi trans-sialidase (TS) antigen. We demonstrate that mice inoculated with these recombinant TS-expressing L. major parasites mount T cell and antibody responses directed against TS and are protected against future T. cruzi infection. We also show that the partially attenuated dhfr-ts- CC1 L. major strain, previously found to induce protective immunity to virulent L. major infection without causing pathology, can also be engineered to express the TS antigen. This latter recombinant may represent a safe and effective option to explore for ultimate use in humans. Altogether, these data indicate that L. major can stably express a T. cruzi antigen and induce T. cruzi-specific protective immunity, warranting further investigation of attenuated Leishmania parasites as vaccine vehicles to protect against T. cruzi and other major human diseases.